Genetic diversity and population structure of pearl millet in the Senegalese germplasm - Aliou Ba; Thomas L. Odong; Richard Edema; Arfang Badji; Oumar Diack; Tony Obua; Mildred Ochwo-Semakula; Paul Gibson; Ndjido. A. Kane; Phinehas Tukamuhabwa (PLoS ONE, 2026)
Pearl millet ( Pennisetum glaucum ), a key cereal for food security in arid and semiarid regions, combines drought tolerance, high nutritional value, and adaptability to marginal environments. In Senegal, numerous landraces have been collected to develop breeding populations. However, genetic diversity and population structure of this germplasm remain poorly understood. This study characterized the genetic diversity and population structure of 169 genotypes, including 15 PMiGAP inbreds lines, 58 F 5 ISMI lines, 94 F 3 PLS lines, and 2 introgressions (29AW and ICMR088888). Genomic DNA was extracted using the CTAB protocol and genotyping was conducted on a DArTseq platform. Following quality control, 16,693 SNPs were retained for downstream analyses. Population structure was inferred using the sparse nonnegative matrix factorization (sNMF) algorithm, and phylogenetic relationships were reconstructed using the Neighbor-Joining method. The mean gene diversity was 0.30, and the average minor allele frequency was 0.21. Four genetic clusters were identified: cluster 1 comprised mainly F 3 lines (88%), while cluster 2 included 56% of F 5 ISMI lines. Nei genetic distances ranged from 0.023 (between clusters 2 and 4) to 0.078 (between clusters 3 and 2). Analysis of molecular variance revealed 92.1% of variation within clusters and 7.9% among clusters. Principal component analysis and fixation index ( F ST ) results were consistent with the structure and phylogenetic analyses. The moderate genetic diversity and clear population structure observed suggest great potential for defining heterotic groups and developing resilient hybrid varieties as well as better conservation strategies.